Elevated Plasma Levels of Crosslinked Fibrinogen Gamma-chain Dimer Indicate Cancer-related Fibrin Deposition and Fibrinolysis - Gerner, Christopher; Steinkellner, Werner; Holzmann, Klaus; Gsur, Andrea; Grimm, Rudolf; Ensinger, Christian; Obrist, Peter; Sauermann, Georg (Thrombosis and Haemostasis, 2001)
Cancer-related fibrin deposition and fibrinolysis were investigated by two-dimensional gel electrophoresis of human solid tumor and effusion specimen in addition to plasma samples. Fibrinogen gamma-chain dimer indicating fibrin deposition and plasmin-generated fibrinogen beta-chain fragments were identified in various solid tumor types by amino acid sequencing, mass spectrometry analysis and Western blotting. In tumor-associated effusions, these techniques allowed to observe plasmin-generated fragments of fibrinogen alpha, beta and gamma-chains in addition to elevated levels of acute-phase proteins. Similar observations were made in case of inflammation-associated effusions. No fibrin degradation product was observed in plasma samples, however, high amounts of fibrinogen gamma-chain dimer crosslinked by transglutaminase were detected in plasma from tumor patients, but not in plasma from controls and patients suffering acute infections and/or inflammations. This finding demonstrated that high transglutaminase activity may be associated with cancer. The presented data indicate that the amount of crosslinked fibrinogen gamma-chain dimer in plasma may correlate with tumor-associated fibrin deposition. The tumor-biological relevance of this potential marker protein is discussed.
Keywords: Cancer; fibrin deposition; fibrinolysis; plasma proteins; two-dimensional gel electrophoresis